Decomposition of intumescent coatings: comparison between numerical method and experimental results - Mesquita, L.M.R. (2010)
An investigation of two different intumescent coatings used in steel fire protection has been performed to evaluate their efficiency. A set of experimental tests is presented. They were conducted in a cone calorimeter, considering different thicknesses and heat fluxes. Among other quantities, the steel temperature and the intumescence thickness variation were measured. A numerical model for the paint decomposition is also presented. Based on the intumescence experimental value, the model is able to provide a reasonably good prediction of the steel temperature evolution.